2022
DOI: 10.1002/slct.202103565
|View full text |Cite
|
Sign up to set email alerts
|

New Sulfur‐Containing Ferrocenylimidazo[4,5‐b]pyridines: Multiresponsive Hg2+ Ion Sensing and Structure‐Sensing Correlation

Abstract: Two new sulfur-containing ferrocenylimidazo [4,5-b]pyridines, 2-ferrocenyl-5-(thiophen-2-yl)-1H-imidazo [4,5-b]pyridine (L1) and 2-ferrocenyl-5-(thiophen-3-yl)-1H-imidazo[4,5-b]pyridine (L2), were synthesized and characterized. L1 and L2 behaved as highly selective fluorescent "turn-off", redox (ΔE 1/2 = 0.25 V for L1 and ΔE 1/2 = 0.22 V for L2) and UV active receptors for Hg 2 + ions through the formation of the corresponding 2 : 1 and 1 : 1 (receptor:metal ion) complexes, with detection limits 4.47 × 10 À 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“… Imidazo[1,5- a ]pyridines are investigated and utilized for their emissive properties (serving as fluorophores) [ 13 , 14 , 15 ] or chelating ligands for metallic ions, contributing to the development of on–off-type sensors [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Imidazo[4,5- b ]pyridines are principally studied for the development of emissive products for OLEDs (organic light-emitting diodes) and sensor applications due to their excellent emissive properties [ 23 , 24 , 25 , 26 , 27 , 28 ]. Imidazo[4,5- c ]pyridines display a bioisosteric resemblance to the purine nucleus, manifesting similar structural and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Imidazo[1,5- a ]pyridines are investigated and utilized for their emissive properties (serving as fluorophores) [ 13 , 14 , 15 ] or chelating ligands for metallic ions, contributing to the development of on–off-type sensors [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Imidazo[4,5- b ]pyridines are principally studied for the development of emissive products for OLEDs (organic light-emitting diodes) and sensor applications due to their excellent emissive properties [ 23 , 24 , 25 , 26 , 27 , 28 ]. Imidazo[4,5- c ]pyridines display a bioisosteric resemblance to the purine nucleus, manifesting similar structural and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazo [4,5-b]pyridines are principally studied for the development of emissive products for OLEDs (organic light-emitting diodes) and sensor applications due to their excellent emissive properties [23][24][25][26][27][28]. 4.…”
mentioning
confidence: 99%
“…The formation of a tight 1:1 adduct by the coordination of the imidazolic basic nitrogen to Pb 2+ , strengthened by the nitrogen atom in the fused pyridine ring, was revealed by the Job's plot, NMR chemical shift changes, and DFT calculations. The utility of this structural unit has been confirmed by the studies on a series of related ionophores, which frequently exhibited a multichannel response to metal ions [1–6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the sensing molecules, a number of nitrogenand sulfur-containing heterocycles have been reported to show selective coordination properties toward specific metal ions [1][2][3][4][5][6][7]. Molina reported that imidazopyridine bearing a ferrocenyl group 1 acts as a triple-channel sensing ionophore, which on addition of Pb 2+ shows a redox potential shift, color change, and fluorescence enhancement [8].…”
Section: Introductionmentioning
confidence: 99%